Immunogenicity of a Recombinant Subunit Vaccine Against Feline Coronavirus: A Comparative Study of Three Different Adjuvants - Dong, Bo; Hu, Wenqian; Zhang, Shuo; Zhang, Xiaodong; Zou, Weijie; Guo, Yina; Lin, Weiming (Iranian journal of immunology, 2025)
Currently, there is no effective vaccine against feline coronavirus infections. The coronavirus Spike (S) protein plays a critical role in viral binding to cell receptors and contains multiple neutralizing antibody epitopes that trigger the host's immune response to combat infection. Selecting an optimized adjuvant is essential to ensure robust vaccine-induced immunity against pathogenic infections. To produce a recombinant S protein for the development of subunit vaccines and evaluate the immune responses elicited by different adjuvants. In this study, we developed three subunit vaccines incorporating distinct adjuvants: Alh, ISA201, and CFA FCoV-SP. BALB/c mice were immunized three times via subcutaneous injections with each vaccine formulation. Serum samples were then analyzed to evaluate S protein-specific IgG levels and cytokine concentrations using enzyme-linked immunosorbent assay (ELISA), assessing the magnitude and nature of the vaccine-induced immune responses. The ISA201 FCoV-SP vaccine induced significantly higher total IgG levels than those in the Alh or CFA groups. All tested protein concentrations resulted in increased serum IgG antibody levels, with the optimal immune dose of recombinant S protein being 15 µg/dose. Additionally, the ISA201 FCoV-SP vaccine led to increased expression of interferon-γ, interleukin-8, and tumor necrosis factor-α. Collectively, our findings suggest that ISA201 serves as the most effective adjuvant for a recombinant S protein subunit vaccine against FCoV. Additionally, the subunit vaccine developed in this study exhibited acceptable immune responses in mice.